2011
DOI: 10.1189/jlb.0211096
|View full text |Cite
|
Sign up to set email alerts
|

Fc receptor-like 5 promotes B cell proliferation and drives the development of cells displaying switched isotypes

Abstract: The biological roles of B cell membrane proteins in the FCRL family are enigmatic. FCRL proteins, including FCRL5, were shown to modulate early BCR signaling, although the subsequent, functional consequences of receptor engagement are poorly understood. We found that FCRL5 surface protein itself was induced temporarily upon BCR stimulation of human, naive B cells, indicating precise control over timing of FCRL5 engagement. Cross-linking of FCRL5 on cells induced to express FCRL5 enhanced B cell proliferation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 43 publications
0
40
1
Order By: Relevance
“…We and others reported that FCRL5 binds intact IgG via a complex mechanism (21,22), and therefore immune complexes may link FCRL5 to the BCR, potentially blocking B cell activation similarly to the inhibitory FcgRIIB. Potential activating functions were also proposed for FCRL5 (23), similarly to FCRL3 (24) and FCRL4 (25), suggesting dual regulatory capacities. The expression level of FCRL5 is low in peripheral B cells, but it is increased in lymphoid tissues (14,16).…”
Section: T He Generation Of B Cell Memory Is An Important Component Omentioning
confidence: 91%
See 1 more Smart Citation
“…We and others reported that FCRL5 binds intact IgG via a complex mechanism (21,22), and therefore immune complexes may link FCRL5 to the BCR, potentially blocking B cell activation similarly to the inhibitory FcgRIIB. Potential activating functions were also proposed for FCRL5 (23), similarly to FCRL3 (24) and FCRL4 (25), suggesting dual regulatory capacities. The expression level of FCRL5 is low in peripheral B cells, but it is increased in lymphoid tissues (14,16).…”
Section: T He Generation Of B Cell Memory Is An Important Component Omentioning
confidence: 91%
“…The poor in vitro response of the FCRL5 + TLM subset to a number of stimuli together with prominent expression of multiple inhibitory receptors suggests exhaustion, possibly in response to chronic Ag stimulus. FCRL5 expression itself could be a mark of previous BCR stimulation, as FCRL5 is specifically induced upon BCR stimulation (23). The type of Ag that drives TLM B cells in healthy individuals remains to be defined.…”
mentioning
confidence: 99%
“…In humans, TLR9 is expressed primarily by plasmacytoid CD (pDC) and B cells [1821]. Reflecting their utility as vaccine adjuvants, B lymphocytes exposed to TLR9 agonists become more susceptible to activation by Ag [2224] while TLR9 stimulated pDC produce type I interferons and more efficiently present Ag to T cells [2527]. Non-human primates (NHP) also respond to the same CpG motifs as humans.…”
Section: Toll-like Receptormentioning
confidence: 99%
“…In a follow up analysis they investigated FCRL5 modulation following exposure to different stimuli and explored the consequences of its ligation on B cell responses. Although naïve B cells isolated from blood modestly upregulated protein levels when exposed to CpG, FCRL5 was markedly induced by anti-Ig co-stimulation (Dement-Brown et al, 2012). By contrast, the addition of T cell-dependent (TD) stimuli in the form of anti-CD40 and IL-2 had little effect.…”
Section: Functional and Regulatory Propertiesmentioning
confidence: 99%